Pengembangan Bahan Ajar Tematik Berbasis Proyek untuk Mengembangkan Keterampilan Berpikir Kreatif dan Karakter Wirausaha Peserta Didik Tunanetra - Siti Fatimah; Budiono , (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2021)
This study aims to develop project-based thematic teaching materials to improve creative thinking skills and entrepreneurial skill of blind students. The design of teaching material development uses the Design Based Research (DBR) approach. The DBR stage of four stages, namely the needs analysis, product design/development, product testing, and reflection. The subjects in this study were 2 blind students at SLB Putra Manunggal Gombong, Kebumen. The instruments used were questionnaire, interview, observation, and test. The data analysis technique uses qualitative descriptive. The results of the study indicate: 1) Project-based thematic teaching materials are suitable for blind students; 2) Project learning using thematic teaching materials effectively improves creative thinking skills and entrepreneurial skill of blind students; 3) The develop in entrepreneurial character of blind students shows a high category with the percentage of 84%, while the increase in students' creative thinking skills shows a moderate category with an N-Gain value of 0.60.